2012
DOI: 10.1007/s12325-012-0015-y
|View full text |Cite
|
Sign up to set email alerts
|

Definition and Outpatient Management of the Very Low-Birth-Weight Infant With Bronchopulmonary Dysplasia

Abstract: Bronchopulmonary dysplasia (BPD), also known as chronic lung disease of prematurity, is the major cause of pulmonary disease in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 72 publications
(48 reference statements)
1
30
0
4
Order By: Relevance
“…We confirmed that one of the most important risk factors mentioned in literature [5], [6], [8], [9], [28], [29], [31] is the GAGE which exists in almost all (all presented in Table I and II) of the models with acceptable accuracy. Most classifiers presented in the literature consist BW EIGHT and RESP IM V parameters.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We confirmed that one of the most important risk factors mentioned in literature [5], [6], [8], [9], [28], [29], [31] is the GAGE which exists in almost all (all presented in Table I and II) of the models with acceptable accuracy. Most classifiers presented in the literature consist BW EIGHT and RESP IM V parameters.…”
Section: Discussionsupporting
confidence: 81%
“…It is most common among children who received prolonged mechanical ventilation to treat respiratory distress syndrome [5], [6] and those with low birth weight. Almost a third of infants with birth weight lower than 1000g [7] are affected.…”
mentioning
confidence: 99%
“…ROP was described as disease warranting laser treatment (type 1 ROP [22]) in infants surviving ≥28 days. BPD was defined as requiring oxygen (1) at 28 days of life regardless of GA and (2) at 36 weeks' post-menstrual age (PMA) in babies with GA <32 weeks [23]. Late-onset sepsis was specified as positive blood culture >48 h after birth, analysed as episodes per 1,000 infant days [24].…”
Section: Methodsmentioning
confidence: 99%
“…Бронхопульмонарна дисплазія/хронічні захворювання легень є фактором ризику та по-требують скринінгу харчування для ідентифікації додаткової оцінки росту зі створенням індивіду-ального плану харчування. Встановлено затрим-ку росту в дітей із БЛД у 30-67 % випадків, яка утримується у 53 % до 4-8 років життя [9,19,31].…”
Section: оглядові статтіunclassified
“…Комітетом з харчування ESPGHAN рекомен-довано 120-140 мг/кг на добу кальцію з високим ступенем біодосяжності, 90 мг/кг на добу фосфа-тів при вигодовуванні грудним молоком [15,19].…”
Section: оглядові статтіunclassified